The Effect of Patriarchal Ideology on Daughter's Character Building in Laura Ingalls Wilder's Little House on the Prairie - Ririn Pratiwi Suharto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2018)
The character of daughter is built by her father patriarchal ideology in patrilineal kinship. For example, that issue was depicted on Laura as a daughter in Laura Ingalls Wilder Little House on the Prairie (1971). This study aims to explain the way of Laura thinking and behaving which are influenced by her father patriarchal ideology. Then, this study aims to explain the success of her father patriarchal ideology on Laura character building in that novel. This study was a kind of library research. The research method of this study was close reading by using feminism approach. The results of this study showed that first, the character of Laura had been built by her father patriarchal ideology through the way of thinking in Little House on the Prairie (1971). Laura had a forward thinking pattern for the future. She also had the ability to think quickly and logically. She also had a similar thought with her father about the animal skill. She was also able to think critically, as an adult about her safety and the Ingalls family. Second, the way of Laura behaving was also built by her father patriarchal ideology. Laura had an affectionate behaviour toward fellow creatures. She was also be nice when she made a new relationship with the stranger people. She also had a polite behaviour to respect others. Third, Laura father patriarchal ideology was successfully influenced her daughter character building in Laura Ingalls Wilder Little House on the Prairie. Pa as Laura father was considered became the protector for Laura and the Ingalls family. He was also positioned as the superior one by Laura, even he was considered became a hero for the Ingalls family. Pa was also considered had an important role by Laura in her life and also the Ingalls family.